Soft Tissue Sarcoma (STS) in Gezira Sudan Presentation, Management and Outcome (Global Journal of Medical Research, 2013)
Objective: The aim of this study is to evaluate the management of soft tissue sarcoma (STS) in Medani teaching hospital & oncology hospital. In aspect of clinical presentation, surgical procedure, use of adjuvant therapy and the outcome of management. Methods: This is a retrospective descriptive study that has been reviewing a 55 patient with soft tissue sarcoma presented to the hospital during the period from January 2010 to August 2012. Results: the mean age is 51 years. The peak age range was 40–60 years, with the most common site affected by soft tissue sarcoma is the lower limbs (43.6%) and common size of presentation more than 15 cm in the greatest dimension (47.3%). (36.4%) of patients presented with past history of excision. MRI and U/S stand as the most common imaging requested (29.1%) and (30.6%) respectively. Excisional biopsy done for the majority of patients (58.2%) in which most of them has clear margin (56.4%).